PENGARUH WAKTU PERENDAMAN ALKALI PADA SERAT AKAR WANGI TERHADAP KEKUATAN TARIK KOMPOSIT BERMATRIKS RESIN POLIURETAN : EFFECT OF ALKALI IMMERSION TIME ON THE TENSILE STRENGTH OF VETIVER FIBER-REINFORCED POLYURETHANE RESIN MATRIX COMPOSITES - Paundra, Fajar; Susanto, Rahmat; Syaukani, Muhammad; Prabowo, Prabowo; Rojikin, Setyo (Jurnal Teknik Mesin, 2025)
Alkali treatment using NaOH solution aims to to enhance the mechanical strength of the composite. This study investigates the effect of varying immersion durations of vetiver root fibers in a NaOH solution on the tensile strength of polyurethane-based composites. The vetiver fibers, serving as reinforcement, were cut to a length of 3 cm and immersed in a 5% NaOH solution for 2, 3, 4, and 5 hours, along with a control group without treatment. After soaking, the fibers were rinsed until reaching neutral pH and dried for three days. The composites were fabricated using the compression molding method under a pressure of 5 bar for 24 hours. Tensile tests were conducted following ASTM D638 standards. The results indicate that alkali treatment affected the surface characteristics of the fibers, including cleanliness and structural changes. The maximum tensile strength of 1.592 MPa was achieved with a 4-hour immersion, whereas the lowest tensile strength of 0.893 MPa was recorded after 5 hours of soaking.